Bulgaria : Accounting and Auditing - World Bank (Washington, DC, 2014)
This report provides an assessment of accounting, financial reporting, and auditing requirements and practices within the enterprise and financial sectors in Bulgaria. The accounting profession is fragmented. There are four different professional associations in the country with the result being low institutional capacity. Furthermore, there is no quality assurance, investigation and discipline process on the work of accountants and financial statement preparers. The auditing profession is better organized with one association mandated by law to manage access to the profession, training, the code of ethics and quality control. Professional education and training on international standards of accounting and auditing requires much improvement for students, accountants, auditors and tax inspectors. This improvement is needed at each of the universities, the professional bodies and the government.